Determinan Nilai Perusahaan Sebelum dan pada Masa Pandemic Covid-19 - Sri Ambarwati; Tri Astuti; Salsabila Azzahra (Bina Nusantara University, 2021)
This study aims to see the condition of companies in the consumer goods industry sector before the pandemic and during the pandemic using indicators such as Current Ratio, Debt to Equity Ratio (DER), Return on Assets (ROA), Return on Equity (ROE), Net Profit Margin ( NPM) and company size against firm value. In the period before and during the Covid-19 PandemicThe method used in this research is quantitative method using secondary data from the company's financial statements for the first quarter until third quarter of 2019 and 2020 using regression method and different test Paired Sample t Test. . The results of this study indicate that (1) the Current Ratio before the Covid-19 pandemic had a significant negative effect on firm value, while Current The ratio during the Covid-19 pandemic did not have a significant effect on the firm value variable, (2) the Debt to Equity Ratio before the Covid-19 pandemic had a significant negative effect on the firm value variable, while the Debt to Equity Ratio during the Covid-19 pandemic had no significant effect on company value, (3) Return on Assets before and during the Covid-19 pandemic did not have a significant effect on the firm value variable, (4) Return on Equity before and during the Covid-19 pandemic had no significant effect on firm value, (5) Net Profit margin has a significant negative effect on firm value before and during pandemi Covid-19, and (6) company size has a significant positive effect on company value before and during the Covid-19 pandemic.